Prevalensi dan Intensitas Ektoparasit pada Sapi yang dipelihara secara Intensif dan Semi Intensif di Kecamatan Pangkalan Susu Sumatera Utara - Aina, Triya; Tambunan, Efida Pima Sari; Syukriah, Syukriah (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
Beef cattle have a major role in meat production and meet animal protein needs. This study aims to identify and calculate the prevalence rate and level of ectoparasite infestation in beef cattle raised intensively and semi-intensively in Alur Measles village and Pangkalan Susu sub-district agricultural village. This research uses exploratory methods with tools such as sweep nets and tweezers. Sweep nets are used to catch ectoparasites flying around the cow’s body, while tweezers are used to pick up ectoparasites attached to the cow’s body. There are four families of ectoparasite consisting of four different types. The most common type of ectoparasite found is Rhipicephalus microplu. The highest attendance rate was seen in semi-intensively raised cows, with the ectoparasite Rhipicephalus microplus present rate reaching 100% which can be categorized as “always present”. Meanwhile, the lowest attendance rate was seen in intensively reared cattle, with the ectoparasite Chryomya megacephala present at a rate of 26%, which can be categorized as ”frequently present”. The highest infestation rate also occurred in semi-intensively raised cattle, with an Rhipicephalus microplus infestation rate of 6.88, which can be categorized as “moderate”. Meanwhile, the lowest infestation rate occurred in intensively raised cows, with an infestation rate of 0.28, which can be categorized as “very low”I.